Revolutionizing assessment: Innovations in website-based test and measurement applications - Siantoro, Gigih; Pramono, Bayu Agung; Wijaya Kusuma, I Dewa Made Aryananda; Ismalasari, Rini; Jayadi, Ika (Jurnal Keolahragaan, 2024)
The success of information cannot be separated from the use of online media; Website is one of the online media that is widely used by organizations to provide information quickly. Unfortunately, there are currently not many websites that directly provide information and can analyze and monitor users. This study aims to develop a physical test and measurement website to provide information and results of biological monitoring of athletes directly. This research uses a method of ten stages of research and development (R and D). The result of this study is that more than 90% of users rated website design, validity, ease of access, and functionality as accessible and excellent. Analyzing test results and measurements also positively impacts satisfaction using the test and measurement website developed by Surabaya State University. This study concludes that although improvements need to be made to this website, but overall this physical test and measurement website facilitates the assessment of test results and physical measurements, which can be seen directly by coaches: athletes, managers, to parents who are given access. Coaches, athletes, and parent organizations must be able to adapt to the use of technology, such as the Web, to support long-term athlete development processes and performance. Following the needs of athletes, identifying athlete achievements from test results and measurements will be easier because test and measurement norms can also be adjusted to the history of test results and measurements.